2020
DOI: 10.1140/epjc/s10052-020-8258-2
|View full text |Cite
|
Sign up to set email alerts
|

$$f(\mathcal {G})$$ Noether cosmology

Abstract: We develop the n-dimensional cosmology for $$f(\mathcal {G})$$f(G) gravity, where $$\mathcal {G}$$G is the Gauss–Bonnet topological invariant. Specifically, by the so-called Noether Symmetry Approach, we select $$f(\mathcal {G})\simeq \mathcal {G}^k$$f(G)≃Gk power-law models where k is a real number. In particular, the case $$k = 1/2$$k=1/2 for $$n=4$$n=4 results equivalent to General Relativity showing that we do not need to impose the action $$R+f(\mathcal {G})$$R+f(G) to reproduce the Einstein theory. As a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…Sec. IV deals with the application of the method to models containing only non-local terms of the topological invariant G. We show that GR is recovered in the special case f (G) ∼ √ G (see also [28]). Furthermore, it is shown that considering a Einstein-Hilbert action corrected with non-local terms of G is just a subcase of the more general theory f (G, −1 G).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sec. IV deals with the application of the method to models containing only non-local terms of the topological invariant G. We show that GR is recovered in the special case f (G) ∼ √ G (see also [28]). Furthermore, it is shown that considering a Einstein-Hilbert action corrected with non-local terms of G is just a subcase of the more general theory f (G, −1 G).…”
Section: Introductionmentioning
confidence: 95%
“…A similar procedure can be applied to models containing only the GB invariant. As discussed in [28], a theory containing only combinations of G can reduce to GR, at least in a cosmological background.…”
Section: Noether Symmetries In Non-local Gauss-bonnet Cosmologymentioning
confidence: 99%
“…One promising sector of modified gravity theories is Gauss-Bonnet gravity [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], in which the Gauss-Bonnet invariant appears in the Lagrangian in a nonlinear way. Also, extensions of general relativity that contain higher orders of the Riemann and Ricci tensors can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, these effective actions can be distinguished in two main categories: Extended Theories of Gravity [35][36][37][38][39][40][41][42] which improve the Hilbert-Einstein action involving higherorder curvature invariants or scalar fields, and Alternative Theories of Gravity, where some basic assumptions of GR are relaxed, as well as the torsionless connection, the metricity or the universal validity of the equivalence principle [43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%